Faktor-Faktor Yang Mempengaruhi Kepuasan Konsumen Produk VCO - Natasya Torondek; Mikke Marentek; Nancy Henrietta Jessamine Mandey; Arief P. Kumaat (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
Virgin Coconut Oil (VCO) is one of the products produced by the Manado State Polytechnic Technology Excellence Center which has large market potential because of its recognized benefits and advantages. (Syah. A. 2005) Virgin Coconut Oil (VCO) is pure coconut oil produced from processing coconut meat without heating so that it produces oil that is clear, not rancid and free from free traces due to heating. However, to maintain and increase sales, it is necessary understand the factors that influence consumer satisfaction in using this product. The aim of this research is to identify and analyze the factors that influence consumer satisfaction for VCO products produced by the Manado State Polytechnic Technology Excellence Center and marketed at the Investment Gallery. The focus of this research is to understand the most significant aspects that influence consumer behavior in the local context. The method used in this research is descriptive quantitative, through observation, questionnaires and documentation. The results of this research show that service quality consists of dimensions of customer satisfaction, namely reliability, responsiveness, tangibility, assurance and empathy and other factors. that influence customer satisfaction, namely product quality, price, service quality, emotional factors, and cost and convenience are aspects that influence consumer satisfaction. Overall, all the influencing factors are in the values that influence consumer satisfaction with VCO products in the Investment Gallery.